Pengaruh Struktur Kepemilikan dan Leverage Terhadap Return Saham - Susilowati, Eko Meiningsih (STIE Surakarta, 2015)
The objective to be achieved in this study was to provide empirical evidence that ownership structure and leverage affected positively the stock return in manufacturing companies in Indonesian Effect Stock (ISE). The population of research was go public companies enlisted in ISE. The sample was taken using purposive sampling technique aiming to obtain sample corresponding to the research objective, consisting of 45 sample companies. The result of research showed that ownership structure variable affected positively the stock return. Meanwhile, leverage variable affected negatively. Ownership structure and leverage simultaneously did not affect stock return variable. The result of determination test showed that ownership structure and leverage could explained a little of stock return variable only